Diagnosis and microecological characteristics of aerobic vaginitis in outpatients based on preformed enzymes - Zhi-liang Wang; Lan-yong Fu; Zheng-ai Xiong; Qin Qin; Teng-hua Yu; Yu-tong Wu; Yuan-yuan Hua; Yong-hong Zhang (Taiwanese Journal of Obstetrics & Gynecology, 2016)
Objective: Aerobic vaginitis (AV) is a recently proposed term for genital tract infection in women. The diagnosis of AV is mainly based on descriptive diagnostic criteria proposed by Donders and co-workers. The objective of this study is to report AV prevalence in southwest China using an objective assay kit based on preformed enzymes and also to determine its characteristics. Materials and methods: A total of 1948 outpatients were enrolled and tested by a commercial diagnostic kit to investigate the AV prevalence and characteristics in southwestern China. The study mainly examined the vaginal ecosystem, age distribution, Lactobacillus amount, and changes in pH. Differences within groups were analyzed by Wilcoxon two-sample test. Results: The AV detection rate is 15.40%. The AV patients were usually seen in the sexually active age group of 20–30 years, followed by those in the age group of 30–40 years. The vaginal ecosystems of all the patients studied were absolutely abnormal, and diagnosed to have a combined infection [aerobic vaginitis (AV) + bacterial vaginitis (BV) 61.33%; 184/300]. Aerobic bacteria, especially Staphylococcus aureus and Escherichia coli, were predominantly found in the vaginal samples of these women. Conclusion: AV is a common type of genital infection in southwestern China and is characterized by sexually active age and combined infection predominated by the AV and BV type.